TANGGUNG JAWAB HUKUM DAN IMPLIKASINYA TERHADAP PENGGUNAAN TEKNOLOGI KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE) DALAM PELAYANAN KESEHATAN DI INDONESIA - Yulianti Wulandari; Mulyana; Diana Nurkarlin (Journal of Hospital Administration and Management (JHAM), 2026)
Indonesia has adopted artificial intelligence (AI)-based technology in healthcare through the Minister of Health Regulation No. 21 of 2020 on the Ministry of Health Strategic Plan 2020-2024. The integration of AI challenges Indonesia's existing healthcare legal framework, which has traditionally been reactive and sector-specific, because AI differs fundamentally from conventional medical interventions. These challenges highlight the need to examine legal liability and its implications for the use of AI in healthcare services in Indonesia. This study employed a normative legal research approach using a literature review and analytical method to examine legal liability and the implications of AI implementation in healthcare services in Indonesia. Under Law No. 17 of 2023 on Health, healthcare professionals remain legally responsible for the services they provide, including empathy, communication, and ethical decision-making when using AI-based health technologies. However, a legal vacuum persists because no specific legal provisions govern liability when AI produces inaccurate diagnoses that harm patients. Since AI is recognized as a legal object rather than a legal subject, it cannot be held legally accountable. Law No. 17 of 2023 does not explicitly regulate the use of AI in healthcare. Consequently, legal uncertainty remains regarding liability for AI-related harm, particularly in determining whether responsibility lies with physicians, operators, developers, or other parties responsible for establishing AI operational parameters. Clear legal regulations are therefore needed to ensure legal certainty, accountability, and patient protection.